Karakterisasi Molekuler Papaya ringspot virus tipe P pada Tanaman Mentimun di Jawa - Listihani Listihani; Tri Asmira Damayanti; Sri Hendrastuti Hidayat; Suryo Wiyono (The Indonesian Phytopathological Society (Perhimpunan Fitopatologi Indonesia), 2018)
Moleculer Characterization of Papaya ringspot virus type P on Cucumber in JavaInfection of Papaya ringspot virus (PRSV) on cucumber plants showing mosaic symptom was detected using specific antibody. Further investigation was conducted to determine molecular characters and status of PRSV infecting cucumber in Java. Infection of PRSV was detected from leaf samples collected from the field using dot immunobinding assay (DIBA). Disease frequency caused by PRSV infection reached 81.11%, 95.86%, 91.66%, and 92.3% in East Java, Central Java, Yogyakarta, and West Java, respectively. Characterization of PRSV isolates was conducted by reverse transcription polymerase chain reaction (RT-PCR) using specific primers for PRSV-P and PRSV-W, followed by cloning, and DNA sequencing. DNA fragment of 470 bp was successfully amplified using specific primers for PRSV-P from several samples from Nganjuk, Brebes, Kulon Progo, and Subang; but no amplification was achieved using specific primers for PRSV-W. Nucleotide and amino acid analysis showed high homology among PRSV-P isolates from Nganjuk, Brebes, Kulon Progo, and Subang, i.e. 98.6%-99.7% and 99.3%-100%, respectively. This is an indication of a low genetic variation among PRSV-P from Java. Further phylogenetic analysis indicated that PRSV-P isolate cucumber is in the same cluster with PRSV-P isolate papaya from Bali, Indonesia. This is the first report of PRSV-P infecting cucumber in Indonesia.